Finger Rehabilitation Support System Using a Multifingered Haptic Interface Controlled by a Surface Electromyogram - Masaaki Hioki; Haruhisa Kawasaki; Hirofumi Sakaeda; Yutaka Nishimoto; Tetsuya Mouri (Journal of Robotics)
This paper presents a new type of finger rehabilitation system using a multifingered haptic interface that is controlled by the patient though a surface electromyogram. We have developed the multifingered haptic interface robot: HIRO III that can give 3-directional forces to 5 fingertips. This robot can also be used as a rehabilitation device that can provide various fingertip exercises and measure various types of information. The sEMG works together with the HIRO III to consider the patient's intent. The proposed system is intended for patients having paralysis in the hand and fingers, and the motions will be provided as biofeedback to the fingertips with the device. In contrast to completely passive rehabilitation, the proposed system can provide active rehabilitation using sEMG. The experiment involved finger opening and closing with this system by ten able-bodied subjects. The results show that almost all subjects felt appropriate motion support from the device.